Higher Taxes for Fiscal Consolidation? Expected and Unexpected Effects of Municipal Tax Policy - Mario Hesse (International Advances in Economic Research, 2022)
During episodes of fiscal consolidation in public budgets, there are different instruments to choose from. The literature shows broad consensus that expenditure cuts are preferred, whereas tax increases tend not to support the fiscal aim. The paper examines instruments for fiscal consolidation at the municipal level in Germany presenting theoretical and empirical findings in favor of revenue-based instruments, focusing on the case of municipalities in the Free State of Saxony. German municipalities can autonomously control several positions on both the expenditure side and the revenue side. Options for expenditure cuts are given both for voluntary and compulsory tasks. On the revenue side, municipalities have the opportunity to set assessment rates on both local trade taxes and property taxes. For this part of the consolidation process, the prevailing opinion is that higher taxes are offset by lower grants, which is not the case in reality. Nevertheless, there are cannibalization effects to consider that may induce primary effects in the short and medium term. Hence, the paper shows an updated view of the drawbacks and opportunities of revenue-based fiscal consolidation. The paper provides evidence for an economic and political discussion that predominantly focuses strongly on the harmful effects of tax increases on the economy.
Keywords: E62; H71; H72; R10; 330; Fiscal consolidation; Municipal budgets; Municipal taxes; Trade tax; Panel regression; Cox regression